2019
DOI: 10.1590/s0100-83582019370100104
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Applied at the Early Reproductive Stage Impairs Seed Production of Glyphosate-Resistant Hairy Fleabane

Abstract: Glyphosate-resistant hairy fleabane [Conyza bonariensis (L.) Cronq.] is one of the most important weeds in the world. Among the factors that make this weed species widely distributed in the most diverse environments is the high seed production capacity and dispersal. Hairy fleabane plants not controlled by herbicide application regrowth and overcome crop canopy, use environmental resources, interfere with crops, and complete their life cycle by producing thousands of seeds and replenishing the seed bank. Manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…Biotypes of C. bonariensis showed results higher than 60% for total germination (Figure 1B) and vigor (Figure 1A). These results are considered high in relation to those found by Piasecki et al (2019a), who reported about 38% germination for glyphosate-resistant C. bonariensis. Germination of hairy fleabane seeds is influenced by the environment (light, temperature, salinity, and depth of sowing), with values ranging from 18 to 32% under ideal conditions (Nandula et al, 2006, Wu et al, 2007Davis and Johnson, 2008).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Biotypes of C. bonariensis showed results higher than 60% for total germination (Figure 1B) and vigor (Figure 1A). These results are considered high in relation to those found by Piasecki et al (2019a), who reported about 38% germination for glyphosate-resistant C. bonariensis. Germination of hairy fleabane seeds is influenced by the environment (light, temperature, salinity, and depth of sowing), with values ranging from 18 to 32% under ideal conditions (Nandula et al, 2006, Wu et al, 2007Davis and Johnson, 2008).…”
Section: Resultssupporting
confidence: 55%
“…Molecular identification of species of the biotypes used in the present study indicated that B01R, B11R, B29R, B17S, and B20S are from the species C. bonariensis. B48S presented different molecular pattern in genotyping analyses, being necessary the complementation with morphological analysis, which was performed by an expert in the field, who concluded that the species in question is C. blakei (Cabrera) Cabrera (Table 1) (Piasecki et al, 2019a). According to Lorenzi (2000), the genus Conyza includes approximately 100 species, which are distributed throughout the world, although they are originated from the Americas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viability and germination potential of C. bonariensis seeds were similar between biotypes within each collection site. The viability of seeds was low (±50% or less) in relation to other studies that have reported viability rates between 65% and 80% in R and S Conyza populations [11,19]. However, there are also cases with lower germination rates [2,23].…”
Section: Discussioncontrasting
confidence: 51%
“…Great efforts have been made to characterize the factors involved in the glyphosate resistance, dispersal, and management of C. bonariensis, including growth analysis and bioecological aspects [10]. In considering its seed biology, there is abundant information regarding Conyza's seed germination growing degree days requirements for different sowing dates (autumn, winter, and spring) and agricultural environments [10], as well as its seed viability [11,15], emergence times over a growing season [16], seed longevity [17], and some aspects related to seed quality, such as factors related to seed production, dead seeds, empty seeds, and dormant seeds, among others parameters [18,19]. However, studies on how stress conditions (cold or heat) affect the seed quality of glyphosate-resistant C. bonariensis-which may contribute to its management by reducing seed persistence, reducing the soil seed bank, and consequently preventing the emergence of weeds at critical times [20]-are scarce.…”
Section: Introductionmentioning
confidence: 99%